Analisis potensi sektor unggulan di kota Bengkulu - Setiawan, Prayoga; Amin Prawiro Madhani; Muhammad Refkhi Al Aqilah; Fikri Dias Basmallah; Yosef Felix Sitorus; Dani Rahmad Setiawan (Universitas Negeri Surabaya, 2025)
The purpose of this research is to find out which sector is the leading sector in Bengkulu City with the analysis period 2018-2023. This research uses LQ, DLQ, Shift-share and Klassen Typology analysis. LQ analysis shows that water supply, waste management, waste and recycling, transportation and warehousing, provision of accommodation and eating and drinking, information and communication, financial and insurance services, real estate, corporate services, government administration, defense and compulsory social security, education services, health services, and social activities, and other services as the base sector. Using DLQ, it was found that there are no prospective sectors in Bengkulu City. Using shift-share, the provision of accommodation and food and beverages, and health services and social activities have fast growth rates, good competitiveness, and are progressive. With the Klassen Typology, water supply, waste management, waste and recycling, and provision of accommodation and food and beverages are advanced and developing sectors. Based on these findings, it is expected that the Bengkulu City Government can focus development on these leading sectors, in order to encourage economic growth.